Epidemiological aspects, clinical manifestations, and prevention of pediatric tuberculosis from the perspective of the End TB Strategy - Carvalho, Anna Cristina Calçada (J Bras Pneumol, 2018)
Tuberculosis continues to be a public health priority in many countries. In 2015, tuberculosis killed 1.4 million people, including 210,000 children. Despite the recent progress made in the control of tuberculosis in Brazil, it is still one of the countries with the highest tuberculosis burdens. In 2015, there were 69,000 reported cases of tuberculosis in Brazil and tuberculosis was the cause of 4,500 deaths in the country. In 2014, the World Health Organization approved the End TB Strategy, which set a target date of 2035 for meeting its goals of reducing the tuberculosis incidence by 90% and reducing the number of tuberculosis deaths by 95%. However, to achieve those goals in Brazil, there is a need for collaboration among the various sectors involved in tuberculosis control and for the prioritization of activities, including control measures targeting the most vulnerable populations. Children are highly vulnerable to tuberculosis, and there are particularities specific to pediatric patients regarding tuberculosis development (rapid progression from infection to active disease), prevention (low effectiveness of vaccination against the pulmonary forms and limited availability of preventive treatment of latent tuberculosis infection), diagnosis (a low rate of bacteriologically confirmed diagnosis), and treatment (poor availability of child-friendly anti-tuberculosis drugs). In this review, we discuss the epidemiology, clinical manifestations, and prevention of tuberculosis in childhood and adolescence, highlighting the peculiarities of active and latent tuberculosis in those age groups, in order to prompt reflection on new approaches to the management of pediatric tuberculosis within the framework of the End TB Strategy.